Maintenance of visual functions in patients with a scheduled cataract surgery - I.A. Il’inskaya; S.Yu. Kopaev (РМЖ "Клиническая офтальмология")
Maintenance of visual functions in patients with a scheduled cataract surgery I.A. Il’inskaya1, S.Yu. Kopaev2 1Pirogov Russian National Research Medical University, Moscow, Russian Federation 2S.N. Fedorov NMRC “MNTK “Eye Microsurgery”, Moscow, Russian Federation Aim: to evaluate the maintenance of visual functions by administering eye drops which prevent lens opacities in patients with a scheduled cataract surgery based on the stages of cataract development. Patients and Methods: 822 patients with a scheduled cataract surgery were recommended with the instillations of Catalin® (1 drop four times daily). The patients were divided into two groups, i.e., the study group (364 patients who used the eye drops throughout the waiting time) and the control group (195 patients who refused the eye drops for various reasons). Both groups were additionally subdivided into three subgroups, i.e., I (mature cataract), II (immature cataract), and III (early cataract). Exclusion criteria (n=263) were irregular instillations or the use of Catalin® analogues. Results: the average waiting time was 6.76±1.35 months. A decrease in uncorrected visual acuity (UCVA) by 37% and 40% was revealed in the study group and the control group, respectively. Additionally, a myopic shift of the spherical equivalent was detected. Significant differences (р<0.001) were revealed in subgroup II, i.e., less changes in the spherical equivalent as compared with the control group and subgroup III. Meanwhile, the changes in UCVA were significantly less in the study group as compared with the control group. Conclusion: Catalin® (Senju Pharmaceutical) is effective in early cataract. In immature cataract, this drug slows down refractive changes. In mature cataract, Catalin® is ineffective. In these patients, the earliest possible cataract surgery is required. Keywords: vision loss, cataract, spherical equivalent, pirenoxine, cataract treatment, cataract surgery. For citation: Il’inskaya I.A., Kopaev S.Yu. Maintenance of visual functions in patients with a sa scheduled cataract surgery. Russian Journal of Clinical Ophthalmology. 2020;20(3):117–121. DOI: 10.32364/2311-7729-2020-20-3-117-121.